Faktor-Faktor yang Mempengaruhi Kinerja Keuangan Perusahaan Perbankan dengan Struktur Modal sebagai Variabel Moderasi - Hutasoit, Rama; Tarigan, Nelly Agustina BR (Jurnal Samudra Ekonomi dan Bisnis, 2024)
This research aims to analyze the influence of good corporate governance (GCG), capital adequacy ratio (CAR), interest rates of Bank Indonesia, liquidity and operational efficiency on the financial performance of banking companies listed on the BEI for the 2020-2022 period, as well as testing the role of capital structure as a moderating variable. The results show that GCG and operational efficiency have a positive and significant effect on financial performance; liquidity has a positive and insignificant effect on financial performance; and, CAR and interest rates of Bank Indonesia have a negative and insignificant effect on financial performance. Other results stated that capital structure was proven to be able to moderate the relationship between GCG and operational efficiency on banking financial performance, but was unable to moderate the relationship between CAR, interest rates of Bank Indonesia, and liquidity on banking financial performance.